Tilapia lake virus (TiLV) from Peru is genetically close to the Israeli isolates - Pulido L.L.H. (2019)
This study was supported by a research grant from National Science and Technology Development Agency (NSTDA), Thailand (P-18-52583). Liseth Lucero Huamancha Pulido acknowledges the financial support from Cienciactiva – Concytec (management agreement N°230-2015-FONDECYT) - Master in Aquaculture Health of Cayetano Heredia Peruvian University. The authors would like to thank P. Meenium and C. Techatanakitarnan for their technical assistance.